The application of X-ray computed tomography for studying root behaviour in compacted soil - Thompson, Mark (2018)
Tomography (CT) offered a distinctive method for visualising undisturbed RSA which was used to develop an understanding of the response of wheat (Triticum aestivum L.) to compaction. The first aim was to assess the impact of soil properties and X-ray scanning parameters have on image quality, and identify which settings are optimum for balancing against acquisition time. The second aim was to investigate how soil compaction affects the growth and RSA of wheat, while also considering the impact of soil texture. The third aim was to test if and how soil compaction alters a roots mechanical properties, and what anatomical changes are responsible for these changes. Using complementary techniques including root tensile strength testing and root sectioning, insights have been gained on the anatomical adaptions of roots and how these changes affect their material properties and behaviour in compacted soil. This will allow more efficient phenotyping of wheat varieties for soil exploration and resource uptake.